1999
DOI: 10.1002/(sici)1521-3773(19990816)38:16<2377::aid-anie2377>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Sensors for the Detection of Alcohols

Abstract: Cooperativity between different noncovalent host-guest interactions is the key for the successful generation of selective supramolecular sensors. A new class of cavitands capable of synergistic CH small middle dot small middle dot small middle dotpi interactions and hydrogen bonding has been designed and exploited for the detection of alcohol vapors using mass transducers (see schematic representation).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
46
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 2 publications
2
46
0
1
Order By: Relevance
“…In fact, according to Kamlet-Taft ␤ parameters, the ability of secondary and tertiary alcohols to act as hydrogen bond acceptor is greater than that of primary alcohols [44,45]. Interestingly, studies performed on primary alcohols with mass sensitive sensors have shown the same trend in complexation as our study [16,17]. In the case of sensors, this is attributable to the increase of unspecific dispersion interaction between the alkyl chains at the lower rim of the cavitands and the alkyl chains of the alcohol.…”
Section: Competition Experimentssupporting
confidence: 71%
See 2 more Smart Citations
“…In fact, according to Kamlet-Taft ␤ parameters, the ability of secondary and tertiary alcohols to act as hydrogen bond acceptor is greater than that of primary alcohols [44,45]. Interestingly, studies performed on primary alcohols with mass sensitive sensors have shown the same trend in complexation as our study [16,17]. In the case of sensors, this is attributable to the increase of unspecific dispersion interaction between the alkyl chains at the lower rim of the cavitands and the alkyl chains of the alcohol.…”
Section: Competition Experimentssupporting
confidence: 71%
“…CH 3 substituents also increase the -basic character of the cavity, making CH-interactions more effective. This effect of the apical substituents has also been observed in mass sensors [16]. Whether the observed behavior is based on steric or electronic reasons is difficult to conclude on the basis of the present experiments.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…(2) To clarify the gas-phase properties of complexes formed by phosphonate cavitands, [9] since one of their applications is gas sensing [10]. The earlier reported results have shown that the phosphonate cavitands are capable of selectively forming complexes with alcohols [11][12][13][14] and ammonium ions [7,15,16], which has just recently led to application of phosphonate cavitands in supramolecular polymers [17], molecular recognition on silicon surfaces [18], and product protection in amine methylation reactions [19]. Number and positioning of the P ϭ O groups at the upper rim and their relative orientation with respect to the cavity are the key host parameters in defining the multiple H-bonding interactions involved in the recognition process [16].…”
mentioning
confidence: 99%
“…7 In these cases, † Université de Bordeaux. ‡ Université Catholique de Louvain, Laboratoire de cristallographie, Unité CSTR, 1, Place Pasteur, B-1348 Louvain-La-Neuve, Belgium.…”
unclassified